PENGEMBANGAN (LKPD) BERBASIS (PBL) MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT KELAS XII.2 SMAN 13 KONAWE SELATAN - Tri Pri Astuti; Saefuddin Saefuddin; La Rudi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Chemistry learning on electrolyte and non-electrolyte solution materials is often hindered by the limited availability of innovative and problem-based instructional materials. This study aims to develop a valid and practical Student Worksheet (LKPD) based on the Problem Based Learning (PBL) model for electrolyte and non-electrolyte solution materials for 12th-grade students at SMAN 13 Konawe Selatan. The study employed the Research and Development (R&D) method using the 4-D model (Define, Design, Develop, Disseminate), limited to the Develop stage. The limited trial subjects consisted of 9 students from class XII.2 selected through purposive sampling based on high, medium, and low cognitive ability categories, along with 1 chemistry teacher. Data were collected through media expert and material expert validation sheets, as well as teacher and student response questionnaires that had undergone content validity prior to use. The results indicate that the developed LKPD obtained a media expert validation score of 91.88% and a material expert validation score of 89.21%, both categorized as highly feasible. The practicality level was demonstrated by a student response rate of 86.28% and a teacher response rate of 94.25%, with a combined average of 90.27% categorized as very good. Based on these results, the PBL-based LKPD is declared valid and practical, making it suitable for implementation as an effective chemistry learning tool at the senior high school level. ABSTRAK Pembelajaran kimia pada materi larutan elektrolit dan non elektrolit kerap terhambat oleh keterbatasan bahan ajar yang inovatif dan berbasis masalah. Penelitian ini bertujuan mengembangkan Lembar Kerja Peserta Didik (LKPD) berbasis Problem Based Learning (PBL) yang valid dan praktis pada materi larutan elektrolit dan non elektrolit untuk peserta didik kelas XII SMA Negeri 13 Konawe Selatan. Metode yang digunakan adalah Research and Development (R&D) dengan model 4-D (Define, Design, Develop, Disseminate) yang dibatasi hingga tahap Develop. Subjek uji coba terbatas terdiri atas 9 peserta didik kelas XII.2 yang dipilih secara purposive sampling berdasarkan kategori kemampuan kognitif tinggi, sedang, dan rendah, serta 1 guru mata pelajaran kimia. Data dikumpulkan melalui lembar validasi ahli media dan ahli materi, serta angket respon guru dan peserta didik yang telah melalui validasi isi sebelum digunakan. Hasil penelitian menunjukkan bahwa LKPD yang dikembangkan memperoleh persentase validasi ahli media sebesar 91,88% dan ahli materi sebesar 89,21%, keduanya dalam kategori sangat layak. Tingkat kepraktisan produk ditunjukkan oleh respon peserta didik sebesar 86,28% dan respon guru sebesar 94,25%, dengan rata-rata gabungan 90,27% dalam kategori sangat baik. Berdasarkan hasil tersebut, LKPD berbasis PBL dinyatakan valid dan praktis sehingga layak diimplementasikan sebagai bahan ajar kimia yang efektif di tingkat SMA.